Numerical modeling of moored floating platforms for wave energy converters using DualSPHysics - Tagliafierro B.; Martinez-Estevez I.; Crego-Loureiro C.; Dominguez J. M.; Crespo A. J. C.; Coe R. G.; Bacelli G.; Viccione G.; Gomez-Gesteira M. (Volume 5A: Ocean Engineering, 2022)
The DualSPHysics open-source code establishes a comprehensive and efficient framework for simulating coastal and ocean engineering structures, which has been proven to be particularly reliable in wave energy converter (WEC) simulation. In this research, the experimental data of the floating oscillating surge wave energy converter (FOSWEC), is used for validation purposes. The FOSWEC2 device developed by SANDIA National Laboratories (US) is quite complex as it has several floating parts, anchor legs and a power take-off system (PTO) connected to the pitching motion of two flaps. Kinetic energy is in fact converted from the relative rotation between the flaps and a movable frame of the platform, setting a significant challenge for the validation of the FOSWEC with time-domain integrated methods. This work proposes a first validation campaign carried out using regular waves, and considering different parameters for the definition of the PTO system. The numerical model prediction for the platform motion (surge and pitch) and the relative flap pitch angle (bow and aft) shows that the model is able to deal with multi-body dynamics interacting with wave-induced forces.